2020
DOI: 10.1080/03088839.2020.1788731
|View full text |Cite
|
Sign up to set email alerts
|

Big data and artificial intelligence in the maritime industry: a bibliometric review and future research directions

Abstract: This study provides a bibliometric review of 279 studies on the applications of big data and artificial intelligence (AI) in the maritime industry, published in 214 academic outlets, authored by 842 scholars. We extracted bibliographical data from the Web of Science database and analysed it using the Bibliometrix tool in R software. Based on citation analysis metrics, we revealed the most influential articles, journals, authors and institutions. Using the bibliographic coupling methodology, we identified four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
107
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(152 citation statements)
references
References 63 publications
1
107
0
6
Order By: Relevance
“…However, the existing digital publishing theories have many defects in dealing with such problems and lack effective means to solve them. erefore, it is necessary to draw on new theories to conduct research on such problems and provide theoretical support for the healthy development of digital publishing enterprises [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the existing digital publishing theories have many defects in dealing with such problems and lack effective means to solve them. erefore, it is necessary to draw on new theories to conduct research on such problems and provide theoretical support for the healthy development of digital publishing enterprises [4].…”
Section: Introductionmentioning
confidence: 99%
“…Ziaul Haque et al [23] shown a bibliometric research on large data and Artificial Intelligence (AI) technologies was examined for 279 studies in maritime industry performed by 842 scholars in 214 university outlets. The bibliographic information was obtained from the science web by researchers and analysed via the R software Bibliometric process.…”
Section: Organizational Risk Assessment Of Cybersecurity Using Aimentioning
confidence: 99%
“…Finally, In maritime shipping from distinct points of view, AI and big data were employed to attain better energy efficiency [66]. A large number of papers concentrated on ship speed optimization [44][52]; while some emphasized vessel crane control [67], and route planning [68].…”
Section: ) Fleet Optimizationmentioning
confidence: 99%